The Krukenberg Procedure: A Surgical Option for the Treatment of Bilateral Hand Amputees - Jha, R; KC, B R; Chand, P (Medical Journal of Shree Birendra Hospital, 2006)
The Krukenberg Procedure: A Surgical Option for the Treatment of Bilateral Hand Amputees